Dielectric method for determination of fat content at 1 GHz frequency - Jilani, M.T. (IEEE Computer Society, 2014)
Food labeling on various product is necessary to fulfill legal requirement as well as for consumer knowledge. In meat products, prevalence of fat content has importance from health perspective. The objective of this study is to determine the fat content of chicken meat using dielectric properties. Microstrip ring resonator based sensor has been used to determine these properties at 1GHz frequency. Experimental results show that there was significant change in effective permittivity with respect to changing the aspect ratios of fat contents. However, this change is negligible after a certain ratio of added-fat, where further addition in fat has no longer effect on its permittivity which can be interpreted as its saturation point. Obtained results from this study have same tendency which reported in literature. Â© 2014 IEEE.